Uncoordinated‐substituents‐induced zinc(II) coordination polymers exhibiting multifunctional fluorescent sensing activity for cations, anions and organochlorine pesticides - Chi, Jie; Zhong, Baoqi; Li, Yan; Shao, Pengpeng; Liu, Guocheng; Gao, Qiang; Chen, Baokuan (Zeitschrift für anorganische und allgemeine Chemie (1950), 2021)
In order to explore the influence of carboxylic acid substituents on the structures and properties of coordination polymers, three new coordination polymers (CPs) of [Zn2(L)2(IP)2] (1), [Zn(L)(HIP)] ⋅ 3H2O (2) and [Zn(L)(NIP)] ⋅ H2O (3) [H2IP=isophthalic acid, H2HIP=5‐hydroxyisophthalic acid, H2NIP=5‐nitroisophthalic acid] were designed and synthesized under hydrothermal conditions with a multi‐torsion‐centered N‐donor ligand of N,N′‐bis(4‐methylenepyridin‐4‐yl)‐1,4‐naphthalene dicarboxamide (L). All three CPs have similar 4,4‐connected two‐dimensional structures exhibiting different structural details, which is induced by uncoordinated‐substituents and discussed systematically. The title CPs 1 and 2 show multi‐functional fluorescent responses towards metal ion (Fe3+), anions (MnO4−, CrO42− and Cr2O72−) and pesticide (2,6‐dichloro‐4‐nitroaniline). The corresponding detection limits are 6.1×10−5 M−1, 3.7×10−4 M−1, 5.5×10−4 M−1, 3.0×10−4 M−1 and 6.7×10−5 M−1 for CP 1, 2.8×10−5 M−1, 4.1×10−4 M−1, 3.0×10−4 M−1, 4.1×10−4 and 2.8×10−5 M−1 for CP 2.